2022
DOI: 10.1002/etc.5444
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Mercury and Radiocesium in Waterfowl Introduced to a Site with Legacy Contamination

Abstract: Despite the propensity of waterfowl species to readily accumulate anthropogenic contaminants within polluted environments, few studies have examined bioaccumulation rates over time when entering such a contaminated site. We examined mercury (Hg) and radiocesium (137Cs) bioaccumulation over time in two waterfowl species released into a wetland system containing legacy contamination on the US Department of Energy's Savannah River Site in South Carolina. Released birds were collected at select time intervals over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Mallards are omnivorous and tend to feed on both plant and animal items (Boreal Songbird Initiative, 2023; Esse, 2008). A recent field study (Leaphart et al, 2022) also found that mallards, but not ring‐necked ducks, introduced into and restricted within a Hg‐contaminated wetland/lake area accumulated Hg in both muscle and liver over a 90‐day study period.…”
Section: Discussionmentioning
confidence: 88%
“…Mallards are omnivorous and tend to feed on both plant and animal items (Boreal Songbird Initiative, 2023; Esse, 2008). A recent field study (Leaphart et al, 2022) also found that mallards, but not ring‐necked ducks, introduced into and restricted within a Hg‐contaminated wetland/lake area accumulated Hg in both muscle and liver over a 90‐day study period.…”
Section: Discussionmentioning
confidence: 88%